Dangerous Places: Gang Members and Neighborhood Levels of Gun Assault. (28th July 2016) - Huebner, Beth M.; Martin, Kimberly; Moule, Richard K.; Pyrooz, David; Decker, Scott H.
Abstract : Despite attention to the role of gangs in urban gun violence, much remains to be learned about the spatial distribution and consequences of residential gang membership. This study uses data from St. Louis to examine the effects of resident gang membership on rates of gun assault. We also consider whether gun violence is conditioned by the level of gang membership in surrounding communities. As anticipated, communities with the highest number of gang members also have the highest rates of gun assault. However, much of the impact of gang membership on gun assaults extends outside of the boundaries of gang neighborhoods, especially those neighborhoods with few or no gang members. The number of gang members in surrounding neighborhoods has no discernible effect on gun assaults in communities with higher rates of gang membership. Finally, controlling for the spatial proximity of residential gang membership helps to account for some of the association between neighborhood disadvantage and gun assaults.